An EAACI position paper on the investigation of perioperative immediate hypersensitivity reactions. Issue 10 (18th June 2019) - Garvey, Lene Heise; Ebo, Didier G.; Mertes, Paul‐Michel; Dewachter, Pascale; Garcez, Tomaz; Kopac, Peter; Laguna, José Julio; Chiriac, Anca Mirela; Terreehorst, Ingrid; Voltolini, Susanna; Scherer, Kathrin
Abstract: Perioperative immediate hypersensitivity reactions are rare. Subsequent allergy investigation is complicated by multiple simultaneous drug exposures, the use of drugs with potent effects and the many differential diagnoses to hypersensitivity in the perioperative setting. The approach to the investigation of these complex reactions is not standardized, and it is becoming increasingly apparent that collaboration between experts in the field of allergy/immunology/dermatology and anaesthesiology is needed to provide the best possible care for these patients. The EAACI task force behind this position paper has therefore combined the expertise of allergists, immunologists and anaesthesiologists. The aims of this position paper were to provide recommendations for the investigation of immediate‐type perioperative hypersensitivity reactions and to provide practical information that can assist clinicians in planning and carrying out investigations. Abstract :